2013
DOI: 10.3998/ark.5550190.0014.306
|View full text |Cite
|
Sign up to set email alerts
|

Unusual direction of three-component reaction involving 2-amino-4-arylimidazoles and carbonyl compounds leading to Knoevenagel-Michael adducts

Abstract: Three-component reaction of 2-amino-4-arylimidazoles, aldehydes and dimedone or barbituric acid proceeds in an unusual direction and instead of imidazo[1,2-a]pyrimidine derivatives gives Knoevenagel-Michael adducts having abnormally low reactivity in heterocyclizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Previously, an unusual direction of the three-component reaction between 2-aminoimidazoles, aldehydes and 5,5-dimethyl-1,3-cyclohexanedione has led to the formation of the Knoevenagel–Michael adducts (Fig. 2) [24]. By analogy with our results obtained with the use of other aminoazoles in the reactions with benzaldehydes and Meldrum’s acid [25] we expected the formation of one or several isomers of tetrahydroimidazopyrimidinone derivatives (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Previously, an unusual direction of the three-component reaction between 2-aminoimidazoles, aldehydes and 5,5-dimethyl-1,3-cyclohexanedione has led to the formation of the Knoevenagel–Michael adducts (Fig. 2) [24]. By analogy with our results obtained with the use of other aminoazoles in the reactions with benzaldehydes and Meldrum’s acid [25] we expected the formation of one or several isomers of tetrahydroimidazopyrimidinone derivatives (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Sometimes the dehydration of dihydro derivatives (reaction I) can occur as a secondary process during their synthesis. [23,87,88] However, it was found that under the conditions of the well-known method of heteroaromatization of dihydroazines by the action of acidic NaNO 2 solutions, electrophilic substitution and formation of oximes (reaction m, Scheme 8) are observed in the case of dihydroazolopyrimidines with R 1 =H. [34,35,55,65] The increased stability of dihydro systems to heteroaromatization processes is also reflected in their relative resistance to the action of atmospheric oxygen and trinitrobenzene.…”
Section: Chemical Properties Of Dihydroazolopyrimidinesmentioning
confidence: 99%
“…The synthesis of 5,6-dihydroimidazo[1,2a]pyrimidines 134 via two component sequential microwaveassisted reactions of 2-amino-4-arylimidazoles 132 with chalcones 133 was described by Andriushchenko et al (Scheme 50). [87] The treatment of thiophene chalcone with 2-aminobenzimidazole in ethanol in the presence of a catalytic amount of AcOH under microwave irradiation was studied in paper. [116] It was found that microwave irradiation was more effective than thermal heating.…”
Section: Reactions Of 2-aminoimidazole and 2-aminobenzimidazolementioning
confidence: 99%
See 1 more Smart Citation